Efficacy of Neurocognitive Rehabilitation After Coronary Artery Bypass Graft Surgery in Improving Quality of Life: An Interventional Trial - Ajtahed, Simin Sadat; Rezapour, Tara; Etemadi, Soraya; Moradi, Hadi; Habibi Asgarabad, Mojtaba; Ekhtiari, Hamed (Frontiers in Psychology, 2019)
Introduction: Cognitive deficits are frequent after coronary artery bypass graft (CABG) surgery and consequently could lead to a decrease in quality of life. This is the first study that has been conducted with the aim of examining the efficacy of a computerized cognitive rehabilitation therapy (CCRT) in improving quality of life in patients after CABG surgery. Methods: In this study, an interventional trial with pre-, post and follow-up assessments in active (CCRT), active control and control groups was conducted. 75 patients after CABG surgery were selected and assigned to the groups (n =25 for each group). CCRT consists of 4 modules of attention, working memory, response inhibition and processing speed training with graded schedule in 20-minute sessions three times per week within 8 weeks. Cognitive functions (attention and working memory) were assessed by the tests of continuous performance, Flanker, useful field of view and digit span at three time points: pre- and post-intervention (T0 and T1) and 6-month follow-up (T2). Quality of life was assessed by the SF-36 questionnaire at the same time points. The CCRT group received the cognitive rehabilitation for 2 months, active control group received a sham version of CCRT in an equal time duration and control group did not receive any cognitive intervention. Results: Repeated measures analysis of variance (ANOVA) revealed a time by group interaction on cognitive functions, with CCRT producing a significant improvement at T1 (p < 0.01) and these improvements were maintained at T2. Moreover, in CCRT and active control groups, QoL improved at T1 and these improvements remained stable throughout follow-up (T2). However, improvement of QoL in CCRT group was greater than improvement of QoL in the other two groups at T1. Pearson's correlation analysis shows a positive correlation between QoL improvement and sustained attention and working memory enhancement (p < 0.05). Conclusion: Cognitive rehabilitation can lead to a significant improvement in the cognitive functions that have been trained in patients receiving CABG. Interestingly enough, cognitive rehabilitation can also improve quality of life in patients after CABG surgery and this improvement is maintained for at least 6 months.